The politics of constructing health data spaces: Border work and the stickiness of fragmentation - Heidrun Åm; Lotte Groth Jensen; Rasmus Mølgaard Hansen; Karoliina Snell; Heta Tarkkala; Aaro Tupasela (Big Data & Society)
This article explores the construction of health data spaces through the lens of border work. It provides insights into the complex attachments and detachments that come to the fore when establishing centralized health data access bodies in the Nordic countries. By comparing Denmark, Norway, and Finland, the study unveils a variety of border work practices. These practices include the complex interplay between national infrastructures, local practices, and regulatory frameworks, the management of continuous attachments through additional loops, and negotiations over public-private borders. The study shows that, despite policy goals envisioning health data access bodies as seamless one-stop shops for ‘detached’ data, the data remains attached to places, institutions, people, and countries. Consequently, new data spaces tend to emerge and co-exist with existing ones. Our analysis of the Nordic experiences offers valuable lessons and critical insights for ongoing efforts to build a European Health Data Space. We further suggest that this stickiness of fragmentation might be a common feature of big data policy efforts.